2021
DOI: 10.1111/jeb.13931
|View full text |Cite
|
Sign up to set email alerts
|

Relaxed selection on male mitochondrial genes in DUI bivalves eases the need for mitonuclear coevolution

Abstract: Almost all eukaryotes rely on mitochondria and mitochondrial (mt)-encoded genes to generate cellular energy via oxidative phosphorylation (OXPHOS) (Karnkowska et al., 2016;Roger et al., 2017). Mt-encoded genes must coordinate with nuclear-encoded mt genes (i.e. N-mt genes) for OXPHOS. Coevolution and coadaptation between mt and N-mt genes are therefore essential and likely a ubiquitous feature of eukaryotes (Havird et al., 2019b;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 118 publications
1
15
1
Order By: Relevance
“…It is worth mentioning that positive selection on M-type has also been reported in other DUI species ( Ort & Pogson, 2007 ; Śmietanka et al, 2009 ), and that selection on M-type inferred by population genetic tests (e.g., McDonald-Kreitman test) and phylogeny-based method (e.g., dN/dS) have been inconsistent in many cases ( Ort & Pogson, 2007 ; Śmietanka et al, 2009 ; Zbawicka et al, 2010 ). In R. philippinarum , phylogenetic analysis indicated relaxed selection on most M-type OXPHOS genes ( Maeda et al, 2021 ), whereas population tests in this study showed a signal of positive selection or balancing selection. Although demographic events or bottleneck differences may influence population-based methods, several genes such as COX3 and NAD3 showed the same signal between the two methods.…”
Section: Discussioncontrasting
confidence: 52%
See 4 more Smart Citations
“…It is worth mentioning that positive selection on M-type has also been reported in other DUI species ( Ort & Pogson, 2007 ; Śmietanka et al, 2009 ), and that selection on M-type inferred by population genetic tests (e.g., McDonald-Kreitman test) and phylogeny-based method (e.g., dN/dS) have been inconsistent in many cases ( Ort & Pogson, 2007 ; Śmietanka et al, 2009 ; Zbawicka et al, 2010 ). In R. philippinarum , phylogenetic analysis indicated relaxed selection on most M-type OXPHOS genes ( Maeda et al, 2021 ), whereas population tests in this study showed a signal of positive selection or balancing selection. Although demographic events or bottleneck differences may influence population-based methods, several genes such as COX3 and NAD3 showed the same signal between the two methods.…”
Section: Discussioncontrasting
confidence: 52%
“…It is worth mentioning that Maeda et al ( 2021 ) found two divergent SDHC sequences in their study and one of them ( SDHC -2) showed a gonad-specific transcription (Supplementary Figure S3B). Around half of the nuclear genes co-transcribed with nuOXPHOS were correlated only with the SDHC -2, which might explain the presence of enriched GO terms involved in the cell cycle (Supplementary Table S6).…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations